2017
DOI: 10.3390/ijms18051055
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Clustering of Adipokines and Hormonal Receptors Predict Prognosis in a Population of Obese Women with Type 1 Endometrial Cancer

Abstract: Obesity is a major risk factor for endometrial cancer (EC). Yet, its impact on prognosis is controversial. Obesity is associated with metabolic and hormonal dysregulation as well as adipokines increase. The aim of this study was to characterize the expression of biological factors related to obesity within the tumor and evaluate their impact on prognosis. One hundred and thirty-six patients, including 55 obese patients, with endometrioid type I EC operated by total hysterectomy were included in this retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Both cytokines have been reported to be increased in endometrial cancer and their pro-inflammatory actions play a role in cancer growth and metastasis by inducing reactive oxygen species and subsequent DNA damage and DNA repair inhibition [18]. IL-6 was found to be overexpressed in the stroma of endometrial cancer cells and TNFα was associated with poor survival [19,20]. However, other studies have not reported such an increase and found no difference in the expression of IL-6 in endometrial cancer and at the various clinical stages [21].…”
Section: Introductionmentioning
confidence: 99%
“…Both cytokines have been reported to be increased in endometrial cancer and their pro-inflammatory actions play a role in cancer growth and metastasis by inducing reactive oxygen species and subsequent DNA damage and DNA repair inhibition [18]. IL-6 was found to be overexpressed in the stroma of endometrial cancer cells and TNFα was associated with poor survival [19,20]. However, other studies have not reported such an increase and found no difference in the expression of IL-6 in endometrial cancer and at the various clinical stages [21].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Endometrial hyperplasia is a pathological condition in the endometrium in the form of increased proliferation of the endometrial glands resulting in changes in the ratio of glands and stroma, shape and size of the gland, the glandular structure increases to 2-3 layers and has the potential to be an atypical form of cells when there is no balance of inhibitors and the initiator of the proliferation of glandular cells. [9][10][11] With the imbalance between estrogen and progesterone where there is a state of Unopposed Estrogen that will cause endometrial thickening. Estrogen hormones known to be produced in the ovaries are also produced on adipose tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, leptin plays a proinflammatory role, contributing to the generation and maintenance of low-grade inflammation, recently also linked to EC [42]. However, literature data regarding circulating levels of adiponectin and leptin in EC report conflicting results [111,123,124]. Increased circulating adiponectin and adiponectin/leptin ratio and decreased leptin concentration were shown to be associated with reduced risk for EC [125].…”
Section: Adipokinesmentioning
confidence: 99%